A sudden water blocking grouting material

By designing a sudden water blocking grouting material composed of multiple components and using instantaneous condensation technology, the problem of poor adaptability of existing grouting materials during construction under water or under moving water conditions is solved, and efficient water blocking and reinforcement effects are achieved under high pressure and high flow rate environments.

CN119735408APending Publication Date: 2025-04-01CHINA ENENG GRP THIRD ENG BUREAU CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023822.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When existing grouting materials are constructed under water or under moving water conditions, they are poor in adaptability and are difficult to meet the water blocking and reinforcement needs in high-pressure and high-flow speed groundwater environments.

Method used

A mutation water-blocking grouting material is used, which consists of silicate cement, mineral blends, coagulation accelerator, water reducing agent, wetting agent, bubble inhibitor, settling time regulator, polynuclear material, inorganic underwater non-dispersible material and organic underwater non-dispersible material. The initial and final settling time is controlled through instantaneous coagulation technology to improve the resistance to dispersion and fluidity.

Benefits of technology

This material exhibits excellent water blocking and reinforcement properties under high pressure and high flow velocity environments, can quickly form strength and avoid dilution by water. It is suitable for grouting projects in complex soil geological environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a sudden water plugging grouting material, which is composed of the following components in parts by weight: 65-80 parts of silicate cement, 10-20 parts of mineral admixture, 5-15 parts of accelerator, 0.2-0.6 parts of water reducer, 0.1-0.4 parts of wetting agent, 0.1-0.3 parts of bubble inhibitor, 0.2-0.6 parts of setting time regulator, 0.4-0.8 parts of polynuclear material, 2-4 parts of inorganic underwater non-dispersible material, 0.01-0.04 parts of organic underwater non-dispersible material; the accelerator is seven aluminum and twelve calcium. The invention adopts instant setting technology, and in addition to having the characteristics of ultra-fine cement grouting material, it also has excellent anti-dispersion, fluidity, interface bonding ability, etc., and does not contain ions harmful to concrete, and can be widely used in grouting projects under flowing water conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grouting materials, and in particular to a sudden water blocking grouting material. Background Art

[0002] Grouting technology is an irreplaceable specialized technology in engineering construction, and grouting materials are the core of grouting construction. Grouting materials can be divided into three categories: chemical grouting materials, physical grouting materials, and composite grouting materials. Commonly used chemical grouting materials include acrylates, water-soluble polyurethane, foamed polyurethane, epoxy resin, etc.; commonly used physical grouting materials include ordinary cement, ultrafine cement, water glass, silica sol, etc.; commonly used composite grouting materials include mixed grouting materials of cement, water glass, and acrylates, etc.

[0003] (1) Cement-based grouting material Cement-based grouting material is a powdery material made by premixing high-strength cementing components, expansion components, preferred graded aggregate components and trace modified components in appropriate proportions in the factory. When used, it only needs to be stirred with water to become a high-strength, non-shrinkage grouting material with uniformity, suitable consistency and self-leveling properties that can meet construction requirements. It can be mainly divided into: ordinary cement grouting material, ultra-fine cement grouting material, silica fume cement grouting material, expansive cement grouting material, and mineral powder ultra-fine cement composite grouting material.

[0004] General-purpose cement mainly refers to the six types of cement specified in GB175-2007, namely, Portland cement, ordinary Portland cement, slag Portland cement, pozzolanic Portland cement, fly ash Portland cement and composite Portland cement.

[0005] Cement grouting materials mostly use silicate cement.

[0006] (2) Ultrafine cement grouting material Ultrafine cement is an ideal high-performance ultrafine cement-based grouting material. It has good permeability and groutability similar to organic chemical grouting fluid, has higher strength and durability, is environmentally friendly, and does not pollute the surrounding environment.

[0007] The slurry made of ultrafine cement of this particle size has good pourability and can penetrate into fine sand and silt mixed layers, silt sand layers and silt soil layers that are generally considered impermeable to cement particles. It can be used at a high water-cement ratio and has a high sand consolidation strength at a high water-cement ratio, which can meet the requirements of grouting reinforcement construction and achieve high durability and low cost.

[0008] It can be used for projects such as building foundation reinforcement in complex soil and geological environments, building structure reinforcement, building waterproofing and leak-proof grouting, and foundation reinforcement of large equipment, and can demonstrate excellent performance.

[0009] The application range of ground cement materials is narrow and the cost is high, so in most engineering practices it is only used as a transition between ordinary cement and chemical grouting materials, and has not been widely used in recent years.

[0010] (3) Non-cement-based inorganic micro-crack grouting materials Non-cement-based inorganic grouting materials are new materials that have only appeared since 2000, but have already shown their potential as a new grouting material. This type of material generally includes two categories, one is high-alkali activated carbonate-slag material, and the other is submicron ultra-micro grouting material.

[0011] (4) Chemical grouting materials Acrylate plugging grouting material is a low-viscosity grouting material made by adding various required components to an acrylate mixture aqueous solution generated by the reaction of excessive metal oxides, hydroxides and acrylic acid. It is mainly composed of calcium acrylate and magnesium acrylate. Under the action of promoters and initiators, double bonds undergo free radical reactions to generate linear polymers. Under the action of cross-linking agents, linear polymers undergo cross-linking to generate grid-like polymer gels. Water interacts with a large number of hydrophilic groups contained in the grid, relying on physical effects such as hydrogen bonds and intermolecular forces to accommodate water several times its own volume. During the curing process, the slurry has an induction period, and the viscosity remains unchanged at the beginning. After the heat release begins, it enters the accelerated polymerization stage and the viscosity increases. Therefore, in the process of using polyacrylate grouting, the mutual influence of the slurry penetration depth under the grouting pressure and the slurry gel time should be considered. Adjusting the grouting pressure and gel time should ensure that the slurry can penetrate in place.

[0012] Water-soluble polyurethane grouting material is a single-liquid chemical slurry composed of -NCO-terminated prepolymers generated by the reaction of polyisocyanates and hydrophilic polyether polyols, and some additives. The slurry has good hydrophilicity, water is used as a curing agent, and there is no pollution to the water quality after grouting. The slurry is driven to fill the gaps by the pressure of secondary foaming of the slurry.

[0013] Cement-water glass slurry is a grouting material formed by injecting cement and water glass in a certain proportion in a double liquid manner, and adding accelerators and retarders when necessary. This slurry overcomes the shortcomings of single-liquid cement slurry, such as long setting time and difficulty in control, and low stone rate under dynamic water conditions, improves the effect of cement grouting, and expands the scope of cement grouting. It is suitable for large water inrush in tunnels, mud plugging, and splitting and consolidation of karst flow plastic soil. The use of this mixed slurry in strata with high groundwater flow rate can achieve the purpose of rapid plugging; it can also be used for anti-seepage and reinforcement grouting.

[0014] Epoxy resin is a common grouting material with many advantages, but its cured body is hard and brittle, which is easy to cause cracking. To solve this problem, elastic epoxy resin was developed. The main principle is to toughen epoxy resin with elastomer, and to toughen it by adding rubber elastomer, thermoplastic resin or other polymer dispersed phase into the epoxy matrix.

[0015] Traditional grouting materials have their own advantages and disadvantages in performance, and their scope of application is also biased. However, when used for grouting and plugging leaks underwater, especially in a pressurized water environment, the presence of mountain water or groundwater requires grouting construction under the action of pressurized water and flowing water, which also puts forward special requirements for grouting materials. It is often necessary for grouting materials to meet the requirements of underwater or dynamic water construction conditions while meeting the requirements of groutability and mechanical properties. At the same time, control requirements are also put forward for the grouting flow range.

[0016] Traditional grouting materials have poor adaptability to this type of working conditions, and new grouting materials need to be developed.

[0017] Cement-based grouting materials: Cement has become the main grouting material due to its good performance, low cost, convenient construction and wide source. However, the use of ordinary cement slurry as grouting material needs to meet four conditions: ① The crack width of the rock mass is greater than 0.2mm, preferably above 0.4mm; ② The water permeability is greater than 1lu; ③ The groundwater flow rate is not greater than 80-100m / d; ④ The chemical composition of the groundwater does not hinder the coagulation and hardening of the cement slurry. It can be seen that it is not feasible to use ordinary cement slurry as a grouting material for fine cracks below 0.2-0.4mm and wide cracks with high groundwater flow rates. Special grouting materials are required for both intervals.

[0018] Chemical grouting materials: 1. Generally, the unit price is high and the engineering cost is high; 2. There are disputes about environmental friendliness; 3. When the groundwater flow rate is high, there is no technical solution that matches the water blocking and strength.

[0019] Therefore, it is necessary to develop a sudden change water plugging grouting material to solve the above problems. Summary of the invention

[0020] The purpose of the present invention is to design a sudden change water plugging grouting material in order to solve the above problems.

[0021] The present invention achieves the above-mentioned purpose through the following technical solutions: A sudden water plugging grouting material is composed of the following components in parts by weight: 65-80 parts of silicate cement, 10-20 parts of mineral admixture, 5-15 parts of accelerator, 0.2-0.6 parts of water reducer, 0.1-0.4 parts of wetting agent, 0.1-0.3 parts of bubble inhibitor, 0.2-0.6 parts of setting time regulator, 0.4-0.8 parts of polynuclear material, 2-4 parts of inorganic underwater non-dispersible material, and 0.01-0.04 parts of organic underwater non-dispersible material; the accelerator is heptaaluminum dodecacalcium.

[0022] Preferably, in silicate cement: the total mass of cement clinker and gypsum is between 80% and 95%, the maximum amount of active mixed materials does not exceed 20% of the hydraulic cementitious material, and the strength includes four grades: 42.5, 42.5R, 52.5, and 52.5R.

[0023] Preferably, the mineral admixture is silica powder or fly ash powder, and the specific surface area of ​​the mineral admixture is 5000m 2 / Kg~10000m 2 / Kg.

[0024] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is greater than or equal to 25%.

[0025] Preferably, the wetting agent is any one of polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, and polyoxyethylene polyoxypropylene block copolymer.

[0026] Preferably, the bubble inhibitor is any one of polyether type, silicone type, and polyether-modified silicone type.

[0027] Preferably, the setting time regulator is tartaric acid.

[0028] Preferably, the polynuclear material is a CSH crystal nucleus with a particle size of 50nm-150nm.

[0029] Preferably, the inorganic underwater non-dispersible material is magnesium aluminum silicate.

[0030] Preferably, the organic underwater non-dispersible material is bio-glue.

[0031] The beneficial effects of the present invention are: The present invention belongs to an organic and inorganic composite grouting material, which adopts instant setting technology and has the characteristics of ultrafine cement grouting material, as well as excellent anti-dispersion, fluidity, interface bonding ability, etc., and does not contain ions harmful to concrete, and can be widely used in grouting projects under flowing water conditions.

[0032] The mutation grouting material uses ordinary silicate cement as the main cementing material with small particle size. At the same time, a certain proportion of nano-grade materials is compounded to improve the permeability of the slurry to small cracks.

[0033] The present invention adopts instant setting technology to control the interval between initial setting and final setting time within 5min-15min; the grouting material has good fluidity before initial setting, and the fluidity loss is small over time. When approaching initial setting, it suddenly loses fluidity and solidifies.

[0034] The present invention uses organic underwater non-dispersible materials to improve the cohesion and flexibility of the slurry, so that the grouting material does not disperse underwater, and the interaction force generated between the grouting stone body and the original substrate is evenly dispersed, avoiding stress concentration again to cause the stone body to be interrupted, ensuring the uniformity of the slurry, and the stone body can maintain the same properties from beginning to end. Magnesium aluminum silicate and biological glue are added to this material, and inorganic and organic materials are used in synergy, and polymers with long straight chains and multi-branched molecules with central nodes are mixed and used in combination. Multi-branched molecules gather and fix material particles around their central nodes in a small area through their rich branches; then the long straight chain polymers connect small areas in series through the winding effect. When the slurry has a tendency to flow, the straight chain molecules are stretched and tightened to produce resistance, thereby enhancing the material's anti-dispersion performance.

[0035] On the one hand, the present invention shows the huge viscosity of the slurry, with an initial viscosity of about 6000mp / s, and the slurry will not be diluted and decomposed by underground or mountain water. On the other hand, the coagulant heptaaluminum dodecahydrate and the coagulation time regulator tartaric acid are used to adjust the coagulation time and hourly strength of the slurry, and the polynuclear material CSH crystal nucleus is used to adjust the early strength of the slurry, thereby controlling the coagulation time and coagulation time difference of the slurry, so that the difference between the initial coagulation and final coagulation time of the slurry is controlled within the range of 5min-15min. After the slurry loses fluidity, it will quickly form strength. DETAILED DESCRIPTION

[0036] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0037] Furthermore, the terms “first”, “second”, etc. are merely used for distinguishing descriptions and are not to be understood as indicating or implying relative importance.

[0038] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms such as "setting" and "connection" should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0039] The specific embodiments of the present invention are described in detail below.

[0040] A sudden change water plugging grouting material, comprising the following components in parts by weight: 65-80 parts of Portland cement; in Portland cement: the total mass of cement clinker and gypsum is between 80% and 95%, the maximum amount of active mixed materials does not exceed 20% of hydraulic cementitious materials, and the strength includes four grades: 42.5, 42.5R, 52.5, and 52.5R; 10-20 parts of mineral admixture; the mineral admixture is silica powder and fly ash powder, and the specific surface area of ​​the mineral admixture is 5000m 2 / Kg~10000m 2 / Kg; 5-15 parts of coagulant; the coagulant is heptadalluminum dodecahydrate; 0.2-0.6 parts of water reducing agent; the water reducing agent is polycarboxylic acid water reducing agent, and the water reducing rate is greater than or equal to 25%; 0.1-0.4 parts of wetting agent; the wetting agent is any one of polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, and polyoxyethylene polyoxypropylene block copolymer; 0.1-0.3 parts of bubble inhibitor; the bubble inhibitor is any one of polyether type, silicone type, and polyether modified silicone type; 0.2-0.6 parts of setting time regulator; the setting time regulator is tartaric acid; 0.4-0.8 parts of polynuclear material; the polynuclear material is CSH crystal nucleus with a particle size of 50nm-150nm; 2-4 parts of inorganic underwater non-dispersible material; the inorganic underwater non-dispersible material is magnesium aluminum silicate; 0.01-0.04 parts of organic underwater non-dispersible material; the organic underwater non-dispersible material is biological glue.

[0041] The invention can control the initial setting time and the final setting time of the grouting material by changing the weight proportion of each component.

[0042] Embodiment 1: The components and their weights of a sudden water plugging grouting material in this embodiment are: 65 parts of ordinary Portland cement, 18 parts of mineral admixture, 14 parts of accelerator, 0.2 parts of water reducer, 0.1 parts of wetting agent, 0.1 parts of bubble inhibitor, 0.2 parts of setting time regulator, 0.4 parts of polynuclear material, 2 parts of inorganic underwater non-dispersible material, 0.02 parts of organic underwater non-dispersible material, and 25 parts of water.

[0043] Embodiment 2: The components and their weights of a sudden water plugging grouting material in this embodiment are: 72 parts of ordinary Portland cement, 14 parts of mineral admixture, 10 parts of accelerator, 0.4 parts of water reducer, 0.3 parts of wetting agent, 0.2 parts of bubble inhibitor, 0.4 parts of setting time regulator, 0.5 parts of polynuclear material, 3 parts of inorganic underwater non-dispersible material, 0.03 parts of organic underwater non-dispersible material, and 30 parts of water.

[0044] Embodiment 3: The components and their weights of a sudden water plugging grouting material in this embodiment are: 80 parts of ordinary Portland cement, 10 parts of mineral admixture, 5 parts of accelerator, 0.6 parts of water reducer, 0.4 parts of wetting agent, 0.3 parts of bubble inhibitor, 0.6 parts of setting time regulator, 0.8 parts of polynuclear material, 3 parts of inorganic underwater non-dispersible material, 0.04 parts of organic underwater non-dispersible material, and 35 parts of water.

[0045] Embodiment 4: The components and their weights of a sudden water plugging grouting material in this embodiment are: 65 parts of ordinary Portland cement, 20 parts of mineral admixture, 11 parts of accelerator, 0.2 parts of water reducer, 0.1 parts of wetting agent, 0.1 parts of bubble inhibitor, 0.2 parts of setting time regulator, 0.4 parts of polynuclear material, 4 parts of inorganic underwater non-dispersible material, 0.02 parts of organic underwater non-dispersible material, and 35 parts of water.

[0046] Embodiment 5: The components and their weights of a sudden water plugging grouting material in this embodiment are: 71 parts of ordinary Portland cement, 10 parts of mineral admixture, 15 parts of accelerator, 0.2 parts of water reducer, 0.1 parts of wetting agent, 0.1 parts of bubble inhibitor, 0.2 parts of setting time regulator, 0.4 parts of polynuclear material, 2 parts of inorganic underwater non-dispersible material, 0.04 parts of organic underwater non-dispersible material, and 35 parts of water.

[0047] The specific selection of the components of the sudden change water plugging grouting material in Examples 1-5 is: Cement: Portland cement with a strength of 42.5; Mineral admixtures: silica powder, fly ash powder, specific surface area of ​​10000m 2 / Kg; Coagulant: hepta-aluminum-dodeca-calcium; Water reducing agent: polycarboxylate water reducing agent, water reducing rate is 25%; Wetting agent: polyoxyethylene fatty alcohol ether; Bubble inhibitor: silicone type; Setting time regulator: tartaric acid; Core material: CSH core, particle size 100nm; Inorganic underwater non-dispersible materials: magnesium aluminum silicate; Organic underwater non-dispersible materials: bio-glue.

[0048] Preparation method: Weigh each component according to the above weight example, mix in a mixer for 10 minutes, and stir at a linear speed of 1.5 m / s to form a product after mixing evenly; Usage: Add an appropriate amount of free water to this material to make its consistency meet the use requirements; during construction, conventional concrete material construction methods are adopted, and it is mainly used for underwater grouting and water blocking projects.

[0049] Comparative Example 1: The raw materials of this comparative example do not contain any mineral admixture, and the rest are the same as those of Example 1.

[0050] Comparative Example 2: The raw materials of this comparative example do not contain a coagulant, and the rest are the same as those of Example 1.

[0051] Comparative Example 3: The raw materials of this comparative example do not contain any inorganic underwater non-dispersible material, and the rest are the same as those of Example 1.

[0052] Comparative Example 4: The mineral admixture in the raw materials of this comparative example is fly ash, and the rest is the same as that of Example 1.

[0053] Comparative Example 5: The raw materials of this comparative example do not contain CSH crystal nuclei, and the rest are the same as those of Example 1.

[0054] Experimental Example: This experiment measured the specific surface area, viscosity, setting time, fluidity, compressive strength, and durability of the grouting materials prepared in each embodiment. The test results are shown in Table 1 below: Table 1: Test results of Examples 1-5

[0055] This experiment measured the specific surface area, viscosity, setting time, fluidity, compressive strength, and durability of the grouting materials prepared in each comparative example. The test results are shown in Table 2 below: Table 2: Test results of comparative examples 1-5

[0056] The results of Example 1-Example 5 show that: (1) A sudden water plugging grouting material, the composition formula of which is as follows: 65-80 parts of ordinary Portland cement, 10-20 parts of mineral admixture, 5-15 parts of accelerator, 0.2-0.6 parts of water reducer, 0.1-0.4 parts of wetting agent, 0.1-0.3 parts of bubble inhibitor, 0.2-0.6 parts of setting time regulator, 0.4-0.8 parts of polynuclear material, 2-4 parts of inorganic underwater non-dispersible material, 0.01-0.04 parts of organic underwater non-dispersible material, and 25-35 parts of water. Its specific surface area is within the range of 390-800m2 / Kg, initial viscosity is within the range of 3000-6000mp / s, initial setting time is within the range of 30-97min, setting time difference is within the range of 8-12min, 2h compressive strength is within the range of 2.1-12.4MPa, 3d compressive strength is within the range of 14.7-22.4MPa, 28d compressive strength is within the range of 37.2-43.6MPa, and the impermeability grade reaches W8. It meets the material requirements of being able to reliably and quickly seal cracks under the conditions of higher pressure, larger flow and higher velocity groundwater.

[0057] (2) The optimal material formula is: 65 parts of ordinary Portland cement, 18 parts of mineral admixture, 14 parts of accelerator, 0.2 parts of water reducer, 0.1 parts of wetting agent, 0.1 parts of bubble inhibitor, 0.2 parts of setting time regulator, 0.4 parts of polynuclear material, 2 parts of inorganic underwater non-dispersible material, 0.02 parts of organic underwater non-dispersible material, and 25 parts of water.

[0058] The results of comparison examples 1 to 5 show that: (1) In comparison example 1, without mineral admixtures, the specific surface area of ​​the material is reduced, the material fineness is insufficient, and it cannot meet the requirements of ultra-fine crack grouting. Other properties have no obvious changes.

[0059] (2) In comparison example 2, without the presence of a coagulant, the setting time and setting time difference of the material are significantly prolonged. At the same time, the strength cannot be formed in 2 hours, which is similar to the performance of ordinary cement grouting materials and cannot meet the requirements of rapid water blocking.

[0060] (3) In comparison example 3, when there is no underwater non-dispersible material, the initial viscosity of the slurry is significantly reduced, and the underwater non-dispersible effect cannot be achieved.

[0061] (4) In comparison example 4, fly ash was used to replace silica fume, and the performance of the grouting material did not change significantly.

[0062] (5) In the case of comparison example 5 without CSH nuclei, the strength of the grouting material decreased significantly in the early (3d), middle (7d), and late (28d) stages, and its impermeability also decreased.

[0063] The present invention specifically has the following working mechanism: (1) Consolidation strength formation mechanism Strength is the basic guarantee of material performance. The system adopts a variety of technical measures to ensure its strength performance and increase its density. The selected cementitious material is ordinary Portland cement dominated by dicalcium silicate and tricalcium silicate.

[0064] Amorphous materials (microsilica powder, fly ash) are added, which can react in alkaline liquids. The mechanism is as follows: amorphous materials have certain activity and need to react under alkaline conditions. In the early stage of hydration, due to the high content of dicalcium silicate and tricalcium silicate in the cement used, the hydration reaction is slower than that of ordinary cement, so its alkalinity increases slowly, and the reactivity of amorphous silicon-containing materials cannot be activated. In this stage, dicalcium silicate and tricalcium silicate react to form a CSH gel skeleton network. As the reaction proceeds, the CSH gel group begins to grow larger and larger, and pores are formed between different gel bodies. The pores contain pore fluids with high alkalinity. In general, gel pores will be formed or developed into capillaries, affecting the density. When the reaction reaches a certain level, the alkalinity of the pore fluid reaches the threshold of the silicon-containing amorphous material, and the reaction can be initiated. The silicon-containing amorphous material reacts with the hydration product calcium hydroxide to form CSH gel. The main reaction area is the pores generated by the initial SCH gel, so the strength and density of the gel are greatly improved.

[0065] (2) Underwater non-dispersion mechanism When ordinary cement grouting material is used for grouting construction, the water pressure of underground or mountain water will have a fatal impact on the grouting effect. One of the major defects of ordinary cement grouting material is that its setting time difference is difficult to control. It is also difficult to control the time difference between the initial setting and the final setting of the grouting material within 30 minutes, not to mention the strength formed after the initial setting. After using ordinary cement grouting material, the grouting material will be diluted by underground or mountain water. If technical measures are used to increase the viscosity of the grouting material, the fluid will lose viscosity after the initial setting, but the strength is insufficient. It will be destroyed by the water pressure of underground or mountain water and powderized, and carried away by the running water without achieving the grouting effect.

[0066] This material is added with magnesium aluminum silicate and bio-glue, and inorganic and organic materials are used in synergy. The long straight-chain polymer and the multi-branched molecules with central nodes are used in combination. The multi-branched molecules gather and fix the material particles around the central node in a small area through their abundant branches; and then the long straight-chain polymer connects the small areas in series through the winding effect. When the slurry has a tendency to flow, the straight-chain molecules are stretched and tightened to produce resistance. The anti-dispersion performance of the material is enhanced.

[0067] The material's mechanism of action is to disperse evenly in the filling slurry through the dispersion of high molecular polymer chains and charges, and to form a water molecule film around the chain through interaction with water molecules, resulting in a spatial molecular grid structure. During the rheological process, the slurry is like a flowing matrix, always maintaining homogeneity and stability.

[0068] (3) Mechanism of action of instant coagulation technology On the one hand, the mutation grouting material shows great viscosity of the slurry, with an initial viscosity of about 6000mp / s. The slurry will not be diluted and decomposed by underground or mountain water. On the other hand, the coagulant heptaaluminum dodecahydrate and the setting time regulator tartaric acid are used to adjust the setting time and hourly strength of the slurry, and the polynuclear material CSH crystal nucleus is used to adjust the early strength of the slurry. Special technology controls the setting time and setting time difference of the slurry, so that the difference between the initial and final setting time of the slurry is controlled within the range of 5min-15min. After the slurry loses fluidity, it will quickly form strength.

[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sudden change water plugging grouting material, characterized in that: The invention is composed of the following components in parts by weight: 65-80 parts of silicate cement, 10-20 parts of mineral admixture, 5-15 parts of accelerator, 0.2-0.6 parts of water reducer, 0.1-0.4 parts of wetting agent, 0.1-0.3 parts of bubble inhibitor, 0.2-0.6 parts of setting time regulator, 0.4-0.8 parts of polynuclear material, 2-4 parts of inorganic underwater non-dispersible material, 0.01-0.04 parts of organic underwater non-dispersible material; the accelerator is heptaaluminum dodecahydrate.

2. The sudden change water plugging grouting material according to claim 1, characterized in that: In silicate cement: the total mass of cement clinker and gypsum is between 80% and 95%, the maximum dosage of active mixed materials does not exceed 20% of hydraulic cementitious materials, and the strength includes four grades: 42.5, 42.5R, 52.5, and 52.5R.

3. The sudden change water plugging grouting material according to claim 1, characterized in that: The mineral admixtures are silica powder and fly ash powder. The specific surface area of ​​the mineral admixture is 5000m 2 / Kg~10000m 2 / Kg.

4. The sudden change water plugging grouting material according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is greater than or equal to 25%.

5. The sudden change water plugging grouting material according to claim 1, characterized in that: The wetting agent is any one of polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether and polyoxyethylene polyoxypropylene block copolymer.

6. The sudden change water plugging grouting material according to claim 1, characterized in that: The bubble suppressor may be any of a polyether type, a silicone type, and a polyether-modified silicone type.

7. The sudden change water plugging grouting material according to claim 1, characterized in that: The setting time regulator is tartaric acid.

8. The sudden change water plugging grouting material according to claim 1, characterized in that: The core material is CSH crystal core with a particle size of 50nm-150nm.

9. The sudden change water plugging grouting material according to claim 1, characterized in that: The inorganic underwater non-dispersible material is magnesium aluminum silicate.

10. The sudden change water plugging grouting material according to claim 1, characterized in that: The organic underwater non-dispersible material is bio-glue.